2007
DOI: 10.1108/17511060710758687
|View full text |Cite
|
Sign up to set email alerts
|

Revealed preference analysis of red wine attributes using polarisation

Abstract: 2009),"Region of origin and its importance among choice factors in the wine-buying decision makingIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…Empirical evidence supports such hypothesis (e.g. Jarvis, Rungie, Goodman, & Lockshin, 2006;Jarvis, Rungie, & Lockshin, 2007a, 2007bKrystallis & Chrysochou, 2010, 2011Singh, Ehrenberg, & Goodhardt, 2008).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Empirical evidence supports such hypothesis (e.g. Jarvis, Rungie, Goodman, & Lockshin, 2006;Jarvis, Rungie, & Lockshin, 2007a, 2007bKrystallis & Chrysochou, 2010, 2011Singh, Ehrenberg, & Goodhardt, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…those with small market shares) to have lower repeat purchase probabilities (Ehrenberg & Goodhardt, 1970;McPhee, 1963). This suggests that loyalty, as an outcome of repeat purchase behaviour, is related to a brand's size and not to any specific characteristics related to its positioning (Jarvis et al, 2007b).…”
Section: Loyalty From a Repeat Purchase Perspectivementioning
confidence: 97%
See 1 more Smart Citation
“…However, grape variety, country of origin, "someone recommended it" and "I tasted the wine previously" are the most relevant and preferred wine attributes by consumers from New World countries such as Australia, New Zealand and the United States (Hall et al, 2001;Loureiro, 2003;Schamel & Anderson, 2003;Charter & Pettigrew, 2006;Lockshin et al, 2006;Boudreaux & Palmer, 2007;Jarvis et al, 2007;Johnson & Bruwer, 2007;Hollebeek et al, 2007;Veale, 2008;Kolyensikova et al, 2008;Cohen, 2009;Cohen et al, 2009;Goodman, 2009). Finally, some studies have found that brand name, label design, price and "it won a medal/award" had a similar perceived relevance by Old World and New World wine consumers (Angulo et al, 2000;Hall et al, 2001;Skuras & Vakrou, 2002;Thomas & Pickering, 2003;Lockshin et al, 2006;Martinez-Carrasco et al, 2006;Mtimet & Albisu, 2006;Perrouty et al, 2006;Boudreaux & Palmer, 2007;d'Hauteville et al, 2007;Jarvis et al, 2007;Johnson & Brower, 2007;Barreiro et al, 2008;Bernabèu et al, 2008;Hertzberg & Malorgio, 2008;Kolyesnikova et al, 2008Casini & Corsi, 2009Cohen, 2009;Cohen et al, 2009;Goodman, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Seen from this perspective, any product category comprises subcategories formed around product attributes, and that each of these subcategories performs differently in terms of loyalty, obtaining its own attribute-based loyalty level (Krystallis & Chrysochou, 2010). In this respect, managing customer loyalty involves working with a bundle of attributes, with the brand name being only one of them (Jarvis et al, 2007). Some studies have tried to explain the relationship of consumption based on the attributes of the product (Ubilava et al, 2011;Jegethesan et al, 2012;Krystallis, 2013;Hahnel et al, 2014;Schuitema & De Groot, 2015).…”
Section: Purchase Decisionsmentioning
confidence: 99%